Hubungan Usia Paritas Dengan Kejadian Ruptur Perineum Di TPMB Lestari Solihati, S.ST Kabupaten Bogor - Ambariani; Pujiati; Lestari Solihati; Alfida Faqih; Alya Fauziah; Selsa Cintya Melani; Wanelis (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Postpartum maternal bleeding is caused by perineal rupture and uterine rupture. Perineal rupture (perineal tear) is an injury to the birth canal that occurs during childbirth, either using or without instruments, and is an indirect cause of maternal death worldwide due to postpartum hemorrhage. Objective: To determine the relationship between age, parity and the incidence of perineal rupture. Method: Using a quantitative method with a cross-sectional design. This study was conducted at the Lestari Solihati Independent Midwife Practice (TPMB), Bogor Regency. The data used are secondary data sourced from medical records of deliveries for the period January-December 2024. The sampling technique used in this study was a total sampling of 419 people. Results and Conclusions: shows that there is a significant relationship between age, parity and the incidence of perineal rupture with a p value (0.000).